STABILITAS STATIS KAPAL IKAN TIPE LAMBUT TERSANJUNG YANG BERPANGKALAN DI PELABUHAN PERIKANAN SAMUDERA AERTEMBAGA KOTA BITUNG PROPINSI SULAWESI UTARA - Pangalila, Fransisco PT (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Ship is water vehicle with any shape and any purpose, mechanically powered or by windvor tug and categorized as a multipurpose platform. It could be operated underwater or in the surface of water and could function merely as a floating static structure.Â  The natural condition is the fish catching area are unpredictable as the wave an current of the water could disturbing the maneuverability and the stabilty of the ship. For that purpose the fish catching ship should have and meet the criterion of robust construction and strong structure to deal with the extreme condition in the sea and also should have a good maneuverability and enough power to make it move steadily. The total lenght of the sample ship Tersanjung are 15.85 m, the width are 2.90 m and inside the ship measured as 1.32 m. The average comparison among the 3 parameters are 5.50 for L/B, 13.05 for L/D and 2.37 for B/D. The coefficient of the Tersanjung ship are Cb=0.58, Cp=0.96, C =0.60 and Cw=0.87.Â  â€œTersanjungâ€ ship has reverse velocity 3.7 second (1 perod). Maximum rolling reaching at 120 with righting moment of 0.21 m.